Gene Expression And Metabonomic Profilings In P53+/- Knockout Mice Following Diethylstilbestrol Treatment - Salleh, Mohd Nazil (2003)
Clastogenic carcinogen diethylstilbestrol (DES) results in a broad of spectrum of toxic and carcinogenic effects in humans and rodents. Female C57BL/6J wild-type mice (23-25g) and female p53 +/1- hemizygous mice were treated with DES (500 umol/kg) i .p., once daily for 4 days. Control animals were treated with the trioctanoin vehicle only. All animals were sacrificed 24 hours after the last dose, and liver, kidney and uterus were harvested and frozen at -80oC . Analysis of differential expression levels of multiple genes involved in apoptosis and cell was performed using cDNA array technology. Reverse Transcriptase Polymerase Chain Reaction (RT-PCR) analysis was carried out in order to verify the expression of these genes. In hepatocytes, murine apoptosis arrays showed three genes: bcl-w, caspase-3 and E2Fl were transcriptionally down-regulated and eight genes: bad, bax, caspase-1, caspase-7, c-myc, p2I, p53 and Rb were up-regulated. In cell-cycle arrays thirteen genes were up-regulated: CDK6, CKK1, Cyclin C, Cyclin D2, Cyclin D3, Cyclin E, Cyclin E2, E2F1, pI6, p19, p21, p57 and Skp1. The greatest change was inp21 gene expression. There was a 3 -fold versus 10-fold increase induction for apoptosis-